ANOMALI HUJAN BENGAWAN SOLO HILIR 1979 – 2017 SERTA KETERKAITANNYA DENGAN EL NIÑO DAN LA NIÑA - Heri Mulyanti; Ayu Kurnia Ratna Sari (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Rainfall anomaly associated with severe drought or flood. The research objective is to identified rainfall anomaly for 1979 – 2017 over Lower Bengawan Solo and its characteristic when El Nino or La Nina occur. Monthly data of 16 stasiuns used to analyze rainfall anomaly related to El Nino and La Nina. At specific years, it is found that wet anomaly occured 50% station (1989, 1995, 1998, and 1999). These years co-occurence with strong La Nina. Dry anomaly found at 1991, 1997, and 2002 which co-occurence with strong or moderate El Nino.